The effect of using the cognitive modeling strategy on the achievement of sixth-grade female students in science - Assistant lecturer. Doaa Reda Dakhel (Peerian Journals Publishing, 2025)
The research aims to identify the effect of using the cognitive modeling strategy on the achievement of sixth-grade female students in science. This study was conducted in Iraq. The research sample consisted of (90) female students. To achieve the goal of the research, the researcher formulated a null hypothesis and adopted the experimental method with partial control with two equal groups, one of which was experimental. The other was a control group and one of those who took the post-achievement test. The researcher intentionally chose the research sample, which is Sumer Primary School for Girls. As for the research group, it was chosen using a simple random drawing method. The two research groups were rewarded statistically. The researcher also prepared the research requirements and the research tool represented by the achievement test, which consisted of (40) test items from Multiple choice type, and its apparent validity and content validity were verified. The stability of the achievement test items was found by two split-half methods and the internal consistency method. The researcher applied the experiment in the second semester (2023-2024). The results of the research showed the superiority of the students of the experimental group who studied according to the cognitive modeling strategy. On the students of the control group who studied according to the usual method of obtaining science subject, and in light of the research results, the researcher presented a set of conclusions, recommendations and proposals.
Keywords: Strategy; Cognitive Modeling; Achievement